Hydrate Deposition on Cold Pipe Walls in Water-in-Oil (W/O) Emulsion Systems - Ding, L.; Shi, B.; Wang, J.; Liu, Y.; Lv, X.; Wu, H.; Wang, W.; Lou, Xia; Gong, J. (American Chemical Society, 2017)
Hydrate deposition is a major concern in the oil and gas industry. This paper studies the hydrate deposition mechanisms in water-in-oil (W/O) emulsion systems using a high-pressure flow loop. The experimental results indicate that the hydrate deposition process can be divided into four stages: the initial formation and deposition, deposit sloughing, secondary formation and redeposition, and deposit annealing. For the first time, a method to quantify hydrate deposits is proposed. The results show that a low temperature , high pressure, high additive concentration, and low water cut decrease the amount of hydrate deposits. The hydrate deposition amount first increase and then decrease with an increasing flow rate. The experimental results demonstrate that the hydrate deposition process is affected by the hydrate formation driving force, wall surface properties, adhesive water amount, mass-transfer coefficient, and flow shear force.